Central Bank Reserve Management Practices : Insights into Public Asset Management from the Second RAMP Survey - World Bank (World Bank, Washington, DC, 2020)
In the summer of 2019, the World Bank Treasury’s Reserve Advisory and Management Partnership (RAMP) conducted its second survey on central banks’ reserve management practices, with a particular focus on governance, accounting, and other operational practices. Understanding these practices is particularly relevant during the COVID-19 crisis, as central banks use their foreign currency reserves to help their countries deal with capital outflows and sharp decreases in exports, tourism, and remittances. On governance, the survey finds that the most common practice is that boards set the investment policy and guidelines, investment committees review the proposals to the board and monitor implementation, and operational units make day-to-day decisions and develop proposals for the board. Central banks have different organizational arrangements for their operational units. The survey results also show that most central banks are well-positioned to provide foreign currency liquidity during the coronavirus pandemic, as they continue to invest their reserves in high-quality fixed-income assets. At the same time, the gradual diversification to nontraditional asset classes continues. The allocation to emerging market bonds, corporate bonds, and mortgage-backed securities of central banks reserves increased slightly since the previous survey. The data show considerable cross-country differences in the way central banks manage their reserves, and in some circumstances, the analysis suggests these differences correlate with respondents’ country income groups and levels of reserve adequacy. Regarding accounting practices, two-thirds of central banks report some degree of implementation of International Financial Reporting Standards (IFRS). The survey also reveals multiple practices to distribute central bank net income to governments. However, data suggest that the transfers of profits between central banks and ministries of finance are not symmetrical—central banks are more likely to distribute profits than to receive financial support in case of losses.